Exploring the career choices of White and Black, Asian and Minority Ethnic women pharmacists: a qualitative study. (26th December 2017) - Howells, Kelly; Bower, Peter; Hassell, Karen
Abstract: Objective: In the UK, a growing number of females entering pharmacy are women from Black, Asian and minority ethnic groups (BAME). Research shows that BAME women are more likely to work in the community sector and be self-employed locums than white women, and Asian women overrepresented in part-time, lower status roles. This study aims to explore the employment choices of white and BAME women pharmacists to see whether their diverse work patterns are the product of individual choices or other organisational factors. Methods: This study analyses 28 qualitative interviews conducted with 18 BAME and 10 white women pharmacists. The interview schedule was designed to explore early career choices, future career aspirations and key stages in making their career decisions. Key findings: The findings show that white and BAME women are influenced by different factors in their early career choices. Cultural preferences for self-employment and business opportunities discourage BAME women from hospital sector jobs early in their careers. Resonating with other studies, the findings show that white and BAME women face similar barriers to career progression if they work part-time. Conclusions: Women working part-time are more likely to face workforce barriers, irrespective of ethnic origin. Cultural preferences may be preventing BAME women from entering the hospital sector. This research is important in the light of current debates about the future shape of pharmacy practice, as well as wider government policy objectives that seek to improve the working lives of health care professionals and promote racial diversity and equality in the workplace.